Identifikasi Teripang Laut (Holothuroidea) dari Perairan Laut Pulau Kabaruan Berdasarkan Identifikasi Morfologi dan DNA Barcoding - Rattu, Ferencia Esananda; Mege, Revolson; Manampiring, Nonny; Roring, Verawati Ida Yani; Gedoan, Sukmarayu; Mokosuli, Yermia (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Indonesia is known with its high biodiversity. One of them is sea cucumber. Various species of sea cucumbers are found in Indonesian sea in Talaud Regency at Kabaruan Island. Identification of sea cucumbers to reveal the biodiversity of sea cucumbers in Kabaruan Island, which is almost unknown. This research was to identify six samples of sea cucumber (Holothuroidea) in Kabaruan Island based on morphology and DNA barcoding using the COI gene. The differences between each species can be seen from the morphological characteristics, the length and width of sea cucumbers, papillae, pattern and color. The results showed that there were 4 species from 6 samples, which is Holothuria leucospilota, Holothuria whitmaei, Eleutherozoa sp., and Holothuria atra. That six samples with the code A1, A2, B1, C1, and C2 have a homology level of 99%-100% with the target nucleotide sequence from GenBank. Meanwhile, the sample’s code A3 has a homology level of 90% with the Eleutheroza sp. so there is a possibility that sample A3 is a new taxa that has the highest similarity to the Eleutheroza sp. From the six samples, it was found that samples A2 and B1 had the highest level of similarity which is 100%. Meanwhile, the samples with the lowest percentage values are samples A3 and B1 and samples A2 and A3, with a percentage value of 82.75%. There were 4 species from six samples found in Kabaruan Island. There is a possibility that Sample A3 is a new species that is similar to Eleutheroza sp.